Radio Enhancing Access to Innovative Technologies and Climate Information Service for Farmers in Ghana - Fiafor, Benjamin; Tanga, Peter (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
AICCRA Ghana and Farm Radio International (FRI) selected Eight (8) radio stations to deliver the interactive radio program. A 3-day design workshop was organized in Kintampo from May 31 to June 02, 2023, and brought together key stakeholders, including farmers, AICCRA-trained extension officers, representatives from the Ghana Meteorological Agency and participants from all 8 selected radio stations. Subsequently, the eight (8) radio stations have cumulatively aired 144 episodes. These 144 episodes include additional episodes aired by each radio station as part of the sustainability strategy of FRI. In terms of radio listenership, two hundred and forty-five thousand, six hundred and three (245,603) — of which 98,241 are women — are estimated to have listened to the radio program across 10 districts.